(3GdHYO GdCNdGbj aj GdJShjb (B/s - (3ejOhf, EjeGfs ((3GdLRGFQ (B: s (3OGQ gheI ddWHGYI hGdfTQ hGdJhRjY(B, s, 2014)
(3jVe GdEWGQ GdYGe ddJShjb, GdCNdGb hCNdGbjGJ GdCYeGd, GdCNdGb aj GdJShjb(B.s
(3HjHdjhZQGajG(B: (3U U(B.239-244s
Keywords: (3GdCNdGb GdJLGQjI s; (3GdJShjbs